2020
DOI: 10.1016/j.jaci.2020.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, open-label extension study of the efficacy and safety of epicutaneous immunotherapy for peanut allergy in children: PEOPLE 3-year results

Abstract: 14 of those (77.8%) maintained an eliciting dose of > _1000 mg at month 38. Local patch-site skin reactions were common but decreased over time. There was no treatment-related epinephrine use in years 2 or 3. Compliance was high (96.9%), and withdrawals due to treatment-related adverse events were low (1%). Conclusions: These results demonstrate that daily EPIT treatment for peanut allergy beyond 1 year leads to continued response from a well-tolerated, simple-to-use regimen. (J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 43 publications
2
58
0
3
Order By: Relevance
“…Epicutaneous immunotherapy involves the administration of the allergen by means of a skin patch. The clinical evidence shows efficacy for epicutaneous immunotherapy as it increases the oral threshold dose in provocation testing after a treatment phase of several months with very good tolerability [31]. A recently published phase-2 placebo-controlled dosefinding study showed statistically significant results with a 10-fold increase in dose in 48% of patients receiving epicutaneous therapy with a patch containing 250 µg peanut protein [29].…”
Section: Epicutaneous Peanut Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Epicutaneous immunotherapy involves the administration of the allergen by means of a skin patch. The clinical evidence shows efficacy for epicutaneous immunotherapy as it increases the oral threshold dose in provocation testing after a treatment phase of several months with very good tolerability [31]. A recently published phase-2 placebo-controlled dosefinding study showed statistically significant results with a 10-fold increase in dose in 48% of patients receiving epicutaneous therapy with a patch containing 250 µg peanut protein [29].…”
Section: Epicutaneous Peanut Immunotherapymentioning
confidence: 99%
“…The specific forms of treatment can also be differentiated on the basis of route of administration. Numerous studies have been published to date on epicutaneous, sublingual, as well as oral immunotherapy (Table 1; [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]) and are discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Enfin, deux études sur l’allergie à l’arachide apportent des résultats intéressants, celle de Kim et al [55] qui démontre clairement le bénéfice au long cours d’une désensibilisation par voie sublinguale, et celle de Fleicher et al [56] qui montre l’intérêt de la voie épicutanée avec le même allergène.
Fig.
…”
Section: Principales Indications En Pédiatrieunclassified
“…40 A recently published follow up report of longer-term EPIT (involving an additional 2 years of treatment after reaching maintenance) in peanut-allergic children demonstrated sustained clinical benefit with high compliance and low discontinuation rates due to adverse events. 41 For the multi-allergic child, the simultaneous oral administration of a combination of food allergens compared with the administration of a single allergen has been studied. Multifood OIT in small phase I trials is shown to be comparable in safety to single-food immunotherapy.…”
mentioning
confidence: 99%